GENETIC VARIATION AND SELECTION CRITERIA FOR SEED YIELD RELATED TRAITS IN RAPE SEED (Brassica napus L.) (Bangladesh Journal of Plant Breeding and Genetics, 2015)
The field experiment was conducted to estimate the genetic variability and correlation between yield contributing traits using 15 rape seed genotypes. The results indicated that the phenotypic variance for all the characters was considerably higher than the genotypic variance denoting little influence of environmental factors on their expression. Characters like 1000-seed weight (12.39, 14.10), days to 50% flowering (18.36, 18.77) and days to maturity (4.63, 5.06) showed low genotypic and phenotypic coefficient of variation. Moderate genotypic and phenotypic coefficient of variation was observed in number of primary branches per plant (20.22, 22.16), length of siliqua (20.84, 20.97), number of seeds per siliqua (30.90, 33.06), number of siliquae per plant (49.34, 49.81) and yield per plant (34.36, 39.98) and high genotypic (67.00) and phenotypic coefficient of variation (68.57) was observed for number of secondary branches per plant. Plant height (85.98%, 30.89), 1000 seed weight (77.14%, 22.41), days to 50% flowering (95.66%, 20.35) and days to maturity (83.85%, 7.82) showed high heritability with low genetic advance which indicated the possibility of non-additive gene action. Number of primary branches per plant (83.22%, 37.99, 636.02), length of siliqua (98.83%, 42.68, 1084.42), number of seeds per siliqua (87.40%, 59.52, 424.22), number of siliqua per plant (98.15%, 100.71, 178.83) and yield per plant (73.87%, 60.84, 4539.97) showed high heritability with high genetic advance and high genetic advance in percentage of mean revealed the possibility of predominance of additive gene effects. Number of primary branches per plant had showed highly significant positive association with number of secondary branches per plant (rg=0.597, rp= 0.537) and yield per plant (rg=0.43). Days to 50% flowering showed significant positive association with seeds per siliqua (rg=0.492; rp=0.436), 1000 seed weight (rg=0.486; rp=0.472) and yield per plant (rg=0.438; rp=0.379). Length of siliqua manifested highly significant positive association with siliqua per plant (rg=0.571; rp=0.514) and significant negative association with yield per plant (-0.471) at genotypic level. Siliqua per plant had highly significant negative association at both genotypic and phenotypic level with yield per plant (-0.697; -0.525) but 1000 seed weight had highly significant positive association with yield per plant both genotypic and phenotypic level (0.893; 0.814). The results of the path analysis revealed that 1000 seed weight (0.766) had the maximum direct effect and the maximum negative direct effect was observed in seeds per siliqua (0.305). In summary, the results suggested that there were some yield related traits such as 1000 seed weight and days to 50% flowering could be selected and used in breeding program for increasing the grain yield of rapeseed.